2021
DOI: 10.1021/jacs.0c12740
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Enhanced Overall Water Splitting Performance by Partial Oxidation of Ir through Au Modification in Core–Shell Alloy Structure

Abstract: Developing efficient bifunctional electrocatalysts for overall water splitting in acidic conditions is the essential step for proton exchange membrane water electrolyzers (PEMWEs). We first report the synthesis of core−shell structure nanoparticles (NPs) with an Au core and an AuIr 2 alloy shell (Au@AuIr 2 ). Au@AuIr 2 displayed 4.6 (5.6) times higher intrinsic (mass) activity toward the oxygen evolution reaction (OER) than a commercial Ir catalyst. Furthermore, it showed hydrogen evolution reaction (HER) cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(141 citation statements)
references
References 37 publications
4
137
0
Order By: Relevance
“…X‐ray absorption near‐edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS) measurements were further carried out for obtaining more information about the electronic structures and atomic coordination environments of the Ir@IrNiO samples. As shown from the Ir L 3 ‐edge XANES spectra (Figure 3c), the white‐line peak position of Ir@IrNiO is a little left‐shifted compared with the reference IrO 2 , suggesting that the total oxidation state of Ir is lower than +4, [ 19,41,44,45 ] and this consistent with the above XPS result. It has been reported that the white line intensity is thought to be proportional to the d orbital density of states, which can be affected by the multiple oxidization states, [ 19 ] and thus, the relatively low white line intensity further confirms the mixed valences of the Ir.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…X‐ray absorption near‐edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS) measurements were further carried out for obtaining more information about the electronic structures and atomic coordination environments of the Ir@IrNiO samples. As shown from the Ir L 3 ‐edge XANES spectra (Figure 3c), the white‐line peak position of Ir@IrNiO is a little left‐shifted compared with the reference IrO 2 , suggesting that the total oxidation state of Ir is lower than +4, [ 19,41,44,45 ] and this consistent with the above XPS result. It has been reported that the white line intensity is thought to be proportional to the d orbital density of states, which can be affected by the multiple oxidization states, [ 19 ] and thus, the relatively low white line intensity further confirms the mixed valences of the Ir.…”
Section: Resultssupporting
confidence: 81%
“…[ 19 ] Moreover, the intensity of the IrO and IrIr bonds are weakened compared with the reference samples of IrO 2 and Ir, suggesting that the SA‐doped Ir and the surface‐loaded Ir particles have a disordered structure. [ 44 ] For the Ni K‐edge EXAFS spectra of Ir@IrNiO in Figure 3f, there are two main peaks located at the same positions as those of the reference NiO, and one belongs to Ni–Ni and the other to Ni–O. Model‐based EXAFS fitting was also completed (Figure S11, Supporting Information), and the coordination number of the NiO bond is 5.16, lower than the standard value of 6 (Table S4, Supporting Information), suggesting a disorder structure of the NiO.…”
Section: Resultsmentioning
confidence: 99%
“…1 Thus, constructing active water oxidation catalysts (WOCs) integrated with proper light-harvesting units is essential to enhance the watersplitting hydrogen production. To date, despite the expensive iridium-based compounds (IrOx, Ir alloys...), 2,3 cobalt species have been proved to be superior and low-cost artificial WOCs, such as Co3O4 nanocrystals, 4 amorphous CoOx and Co(OH)x, 5,6 and single-site Co complexes. 7,8 Unfortunately, the waste of bulk metal sites, the lack of structural accuracy and regularity, or the contradiction between high loading amount and monodispersity in these forms of Co species, respectively, cause difficulties to understand the structurecatalysis relations and maximize the overall catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This combination reflects more deeply the coordination environment and the coordination bond length of a SRE. [140] For example, the strain in the IrO X layer of this CoIr@IrO catalyst has been identified using this method (Figure 10j), [141] where an increase of the IrO bond length via the addition of layer number of the shell weakens the strain intensity in this core-shell structured catalyst (Figure 10k). In another example, the lattice parameters of a series of PtNi alloys were measured by means of XRD in the first step, confirming a decrease of Reproduced with permission.…”
Section: Strain Characterizationmentioning
confidence: 99%
“…Hence, different Pt SREs have been designed and synthesized (Table 2). [52,86,117,126,141,161,183,[191][192][193][194][195][196][197][198][199][200][201][202][203][204] For example, the Ru@Pt nanoparticle (Figure 17c) has a compressive Pt shell (skin) (Figure 17d), due to a smaller lattice parameter of Ru than that of Pt. [191] This SRE exhibited superior HER performance than a pure Pt foil and a RuPt alloy in both acidic and alkaline solutions.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%